Combat Vehicle Simulator Based on HLA prototype concept - Brožek, Josef; Jakeš, Martin; Karamazov, Simeon; Hamerník, Dan (IEEE (Institute of Electrical and Electronics Engineers), 2016)
A combat vehicle simulator is the first complex drivesimulator developed at the University of Pardubice. It consists of dozens of complementary simulators and simulation calculations. The whole simulator is created on a modified implementation of a game engine. That has resulted in a high-quality graphic processing, based on a hybrid kernel of the simulator (discretecontinuous simulation), which is fully controlled by the developer. The created simulator is built on the HLA architecture. Complex simulators take care of the environment and its creation, weather, physics, firing mechanisms, motion control, inputs and outputs of the emulated environment etc.
Simulátor bojového vozidla postavený na architektuře HLA
Keywords: HLA, High Level Architecture, Simulation, Vehiculra Simulator, Trainer, Game Engine.; HLA, simulace, simulace vozidla, trenažér, herní engine